Smart cross-layer protocol integration for efficient wireless communications. (2015) - Ortiz, Antonio M.; Olivares, Teresa; Royo, Fernando; Crespi, Noel; Orozco-Barbosa, Luis
The integration of protocols from different layers enables efficient wireless communications. Wireless sensor networks (WSNs) represent the core of the internet of things (IoT). The growing number of nodes composing these networks requires effective node synchronisation and a correct network organisation in order to ensure data delivery to the destination nodes. This paper presents a cross-layer approach that integrates a synchronous TDMA MAC protocol with a smart routing approach, oriented to guarantee efficient communications of a set of wireless devices in the IoT. First, both approaches are detailed and individually tested by comparing them to similar approaches in the literature. Then, the cross-layer integration is described and tested, showing that both protocols are able to enhance the network performance when working together.